An experimental investigation of sorption of copper on sandy soil by laboratory batch and column experiments. (1st January 2014) - Saha, Provat K.; Badruzzaman, A.B.M.
In this study, the sorption and transport behaviour of copper in sandy soil has been studied by laboratory batch and column experiments. Partitioning coefficient ( kd ) of copper on sandy soil has been determined by laboratory flow-through (or column) method. Analytical model CXTFIT (2.0) (Toride et al., 1995) and the method of moment (MOM) solutions of Das and Kluitenberg (1996) were used to determine the transport parameters of the column experiments. Results from this study show that sorption behaviour of copper in sandy soil varies with different factors like pH, ionic strength, presence of organic matter in soil, etc. High regression coefficients ( r 2 ) suggest that both Langmuir and Freundlich models are suitable for describing the sorption of copper, but it is limited to low to neutral pH range. Pseudo second order kinetic model can describe the copper sorption kinetics more accurately compared to pseudo first order kinetic model. The calculated partitioning coefficient ( K d ) value of copper from column experiments data is found to be dependent on input copper concentration.